2007
DOI: 10.1074/jbc.m701555200
|View full text |Cite
|
Sign up to set email alerts
|

D1 and D2 Dopamine Receptor Expression Is Regulated by Direct Interaction with the Chaperone Protein Calnexin

Abstract: As for all proteins, G protein-coupled receptors (GPCRs) undergo synthesis and maturation within the endoplasmic reticulum (ER). The mechanisms involved in the biogenesis and trafficking of GPCRs from the ER to the cell surface are poorly understood, but they may involve interactions with other proteins. We have now identified the ER chaperone protein calnexin as an interacting protein for both D 1 and D 2 dopamine receptors. These proteinprotein interactions were confirmed using Western blot analysis and co-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 47 publications
10
57
1
Order By: Relevance
“…B1R was found to interact with calnexin, a chaperone that promotes both of the above functions, which suggests that this chaperone participates in B1R folding control. This is consistent with work on the D1 and D2 dopamine receptors, which were also found to interact with calnexin in HEK293 cells [27]. The same study showed that overexpression of calnexin resulted in decreased cell surface receptor expression, and the receptors mostly appeared in discreet punctate oval-like clusters within the cell [27].…”
Section: Discussionsupporting
confidence: 87%
“…B1R was found to interact with calnexin, a chaperone that promotes both of the above functions, which suggests that this chaperone participates in B1R folding control. This is consistent with work on the D1 and D2 dopamine receptors, which were also found to interact with calnexin in HEK293 cells [27]. The same study showed that overexpression of calnexin resulted in decreased cell surface receptor expression, and the receptors mostly appeared in discreet punctate oval-like clusters within the cell [27].…”
Section: Discussionsupporting
confidence: 87%
“…N-glycosylation has been found to regulate some GPCRs with regard to their export trafficking [6] (Li et al, in press), ligand-induce internalization [7] (Li et al, in press) and degradation [8] (Li et al, in press). Recently, specific sugar binding receptors (lectins) have been shown to be important for the surface expression of membrane proteins including GPCRs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to existing as unique receptors, dopamine receptors can also couple with other proteins and receptors to form functional heterodimers that activate signaling cascades, independent from those activated by each component receptor (Maggio et al, 2009;Missale et al, 2010). Dopamine receptors also form heterodimers through direct protein-protein interactions between D1 and D2 receptors (Free et al, 2007;Pei et al, 2010;Perreault et al, 2010;So et al, 2009), D1 and D3 receptors in the striatum (Ridray et al, 1998;Schwartz et al, 1998), D2 and D5 receptors (O'Dowd et al, 2013;So et al, 2009), D1 receptors and NMDA receptors (NMDARs) Pei et al, 2004), and D5 and GABA-A receptors (Liu et al, 2000), among other transmembrane and cytoplasmic proteins. Dopamine D1 and D2 receptors couple in this manner and the functional heterodimer may play a role in the pathogenesis of major depressive disorder (MDD) (Pei et al, 2010;Wong and Liu, 2012).…”
Section: Introductionmentioning
confidence: 99%